Violence against Women in Kentucky - CAROL E. JORDAN (University Press of Kentucky, 2014)
If an author must identify the moment when she decided to write a book, for me, it was when I was speaking to a group of women’s advocates and they were astonished by the stories I told of the legislative reforms we had made over the past decades. They knew nothing of them. And it was the moment when I noticed that the phone was not ringing as often with people calling to ask me when we had passed a particular piece of legislation addressing rape, domestic violence, or stalking. I took the absence of the ringing phone to mean that this generation of advocates and practitioners was beginning to take reforms for granted, that they did not understand that the protections and services they count on daily were not always available. And it was the moment when a supportive legislator asked me why we advocates were less visible in the halls of the state capitol. And it was certainly the moment when a favorite colleague asked me to write our history. Admittedly, that is four moments, but sometimes it takes repeated encouragement to undertake an awesome task. This book is a history, a chronicle of legislative reforms related to domestic violence,* rape, and stalking. In addition to articulating what a book offers, it is important for an author to be clear about what a book cannot achieve. This book, for example, cannot provide a total history of women in Kentucky. To provide context, there are snippets of women’s history in Kentucky, but the complete story will not be found here. Nor is this book a comprehensive look at the violence against women movement in Kentucky; it is much more narrowly focused on the legislative reforms we have achieved. As this book goes to print, there are still more stories to be told about our movement, more of a history to be written about the development of domestic violence programs, rape crisis centers, adult protective services reforms, innovative policies, and more. I encourage my readers to make sure those stories are written. This book is a selective look at legislation—just over 100 bills—that I believe impacted the violence against women movement in Kentucky. Arguably, other advocates could point out important bills that should have been included and perhaps some that should have been left on the cutting room floor